Femtosecond laser inscription of ultra-compact Mach-Zehnder fibre cladding interferometer incorporating FBG - Theodosiou, Antreas; Ioannou, Andreas; Kalli, Kyriacos (My University, 2018)
Femtosecond laser inscription is used to combine a cladding located Mach-Zehnder interferometer and fibre Bragg grating as a compact and integrated optical fibre sensor. We present results for the sensors' temperature and humidity response.
Keywords: Femtosecond lasers; Fiber optic sensors; Interferometers; Optical fibers; Fiber Bragg gratings